Don't hold me back : my life and art - Rembert, Winfred (Cricket Books, 2003)
Through words and paintings, an artist tells about growing up on a cotton plantation in Cuthbert, Georgia, serving time in prison for his actions during a civil rights demonstration, and finding a purpose and direction in life.